Pengaruh Mendongeng Di Rumah Pada Kemampuan Anak Membaca Nyaring Di Depok - Lestari, Mas Roro Diah Wahyu; Setiowati, Grandi Dwi; Hikmah, Nurlaili (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this study was carried out to find out the achievements of 12 students in reading aloud before and after the experiment of fairytale method assistance conducted by parents at home and to know how much influence parent storytelling assistance has on the achievements of 12 students who experienced delays in reading aloud. Researchers used quasi-experimental one group pretest n posttes. Data collection using tests that are then processed using the statistic t-test. This research activity collaborates with their parents to be willing to do storytelling assistance activities for their children for 2 weeks. The results of data processing found a difference in the average reading ability of pre-test and post-tests in 12 children who experienced a delay in reading aloud by 5.4. T-test results obtained a significance value of 0.00 less than 0.05 then the test results were received. This research has proven the influence of storytelling treatment on the increasing ability to read aloud children, especially in children who experience delays in reading.